University and society: social responsibility, between ethos and practices of resistance - Velásquez Moreno, Jairo Rodrigo; Cortés Salcedo, Ruth Amanda (Emerging Trends in Education, 2025)
INTRODUCTION: This article derives from doctoral research, which shows that both discourses and practices related to university social responsibility (USR) are permeated by a neoliberal political rationality that at the same time has a correlate in the practices of counter-conduct within higher education institutions (HEI). METHOD: It was focused on governmentality studies, where the event of the USR that burst into university management was analyzed according to three key elements, political rationality, the ends and the effects that occur in relation to the processes of subjective production. RESULTS: The RSU is in tune with the interests of advanced liberalism, which make use of autonomy and responsibility. They are in a double perspective, between an ethics of others, as part of a formative profile, and an ethics of the self, framed in processes of subjectivity. DISCUSSION: The RSU uses neo-pastoral technologies based on guilt, which lead to the responsibility of institutions and individuals being in line with the interests of government technologies from the perspective of advanced liberalism.